Business zakat compliance behavioral intention in a developing country. Issue 2 (2nd January 2020) - Saad, Ram Al Jaffri; Farouk, Abubakar Umar; Abdul Kadir, Dzarfan
Abstract : Purpose: This study aims to examine the factors influencing the intention to comply with business zakat in a developing country. Design/methodology/approach: A sample of 700 small and medium scale businessmen was drawn using the random sampling method. A total of 524 responses was analyzed using the partial least square structural equation modeling (PLS-SEM) technique. Findings: Results indicate attitudes toward zakat evasion, attitudes toward moral reasoning, peer influence, zakat knowledge, zakat distribution and perceived zakat board capital positively and significantly influence intention to pay zakat. Interestingly, the enforcement of zakat law was found to significantly influence intention but in a negative direction. Practical implications: Accordingly, it was recommended for policymakers to pay more attention to policy formulation to the identified factors in line with the results so that zakat collection could be increased. Originality/value: The study contributes generally to zakat compliance knowledge and specifically to zakat on business wealth in Muslim majority states in developing countries that are fighting against poverty. The PLS-SEM method and its application in the Islamic field study, especially on zakat payment has a limited discussion in previous studies, which is a unique contribution of this study.